Nursing Care in Mrs. P with Warm Water Footbath Technique at Wangon Public Health Center, Banyumas Regency - Rini Yulia Wardani; Tin Utami (Viva Medika, 2024)
Hypertension during pregnancy is a major cause of high maternal, fetal, and neonatal morbidity and mortality. One intervention to reduce high blood pressure is warm water footbath therapy. Soaking the feet in warm water provides a sense of comfort, where the warm sensation on the skin stimulates endorphin hormones, inducing relaxation and reducing stress. This case study was conducted to determine the effect of warm footbath therapy on lowering blood pressure in pregnant women with hypertension in the working area of the Wangon Public Health Center, Banyumas Regency. The method used was a descriptive case study. The subject was a pregnant woman with hypertension, gestational age ≥ 20 weeks, and blood pressure of 140/90 mmHg. The population in this study was 1 person, using a total sampling technique. The results showed changes in blood pressure in the pregnant woman with hypertension before and after receiving warm water footbath therapy.